The Quantitative Analysis of Formaldehyde Content in Tuna using Chromatropic Acid Reagent : Analisis Kandungan Formalin pada Sampel Ikan Tongkol di Pasar LKMK Siwalankerto Surabaya - Banafsa Fara Nurhawada; Cicik Herlina Yulianti (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Tuna is one of the main food sources for humans which has a high enough water content (69,40%), so it decomposes more quickly. Misuse of formalin in tuna by irresponsible fish sellers in the market, aims to make tuna last longer. The purpose of this study was to analyze the level of formalin in tuna which is suspected to contain formaldehyde using chromatropic acid as a reagent. Therefore, chromatropic acid in strong acid conditions produces purplish-red or violet-red complex compounds and provides chromophore groups or conjugated bonds in formalin compounds to be analyzed quantitatively using UV-Vis Spectrophotometry. The research design began with total sampling of tuna in the LKMK Siwalankerto market in Surabaya, then continued with tuna preparation and sample filtrate was obtained for formalin testing using chromatropic acid reagent using UV-Vis spectrophotometry method at maximum wavelength. Based on the research that has been done, it is known that 3 samples of tuna from the LKMK Siwalankerto market in Surabaya showed no absorption in UV-Vis spectrophotometer measurements at a wavelength of 572 nm. Thus, it can be concluded that no formalin was found inthe sample of tuna at the LKMK siwalankerto market in Surabaya.